2016
DOI: 10.11648/j.avs.20160402.12
|View full text |Cite
|
Sign up to set email alerts
|

Anti-coccidial Activity of Moringa Oleifera Plant

Abstract: Abstract:Moringa Oleifera leaves were screened for its toxicological effect and some pharmacological activities in broiler chicken. Toxicological effect was studied using upgrading oral doses of 75% ethanolic extract in different groups of mice with monitoring the toxicological symptoms and mortality rate. The anti-coccidal activity of Moringa Oleifera powdered leaves for prevention and its 75% ethanolic extract for treatment of coccidiosis were studied in broilers. The obtained result proved that there were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Herbal remedies may be an option for treating coccidiosis in chickens, with the drumstick tree ( M. oleifera ) showing promise. Banna et al [ 117 ] found that adding M. oleifera powder (0.5 and 1%) to broiler feed was extremely effective in reducing coccidiosis symptoms associated with experimental infection with mixed Eimeria species and was comparable to diclazuril (1 ppm). According to Banna et al [ 117 ], M. oleifera has a strong anticoccidial activity and may be a viable option for the prevention of avian coccidiosis in chicken production.…”
Section: Anticoccidial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Herbal remedies may be an option for treating coccidiosis in chickens, with the drumstick tree ( M. oleifera ) showing promise. Banna et al [ 117 ] found that adding M. oleifera powder (0.5 and 1%) to broiler feed was extremely effective in reducing coccidiosis symptoms associated with experimental infection with mixed Eimeria species and was comparable to diclazuril (1 ppm). According to Banna et al [ 117 ], M. oleifera has a strong anticoccidial activity and may be a viable option for the prevention of avian coccidiosis in chicken production.…”
Section: Anticoccidial Activitymentioning
confidence: 99%
“…Banna et al [ 117 ] found that adding M. oleifera powder (0.5 and 1%) to broiler feed was extremely effective in reducing coccidiosis symptoms associated with experimental infection with mixed Eimeria species and was comparable to diclazuril (1 ppm). According to Banna et al [ 117 ], M. oleifera has a strong anticoccidial activity and may be a viable option for the prevention of avian coccidiosis in chicken production. In addition to its growth-promoting effect, safety, and antibacterial action, it may be used as a preventative and curative agent for coccidia.…”
Section: Anticoccidial Activitymentioning
confidence: 99%
“…The methanolic crude extracts of V. officinalis and P. glabrum exhibit antioxidant activity ( Casanova et al, 2008 , Raja and Ramya, 2017 ), which supports the reduction in oocysts shedding in the effective groups. The natural products usually don’t harm a living being with some exceptions, as El Banna, (2016) said that Moringa olifera doesn’t lead to any toxic effect. Similarly, the chicks under trial don’t bear any negative pressure of V. officinalis and P. glabrum methanolic extracts except for the higher concentration (15 mg/ml) of V. officinalis , which yields better FCR but negatively affected the blood and serum profile severely, the exact reason of which is unclear but may be possible due to overdose.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoprophylaxis, is one of the traditional strategies to control parasitic diseases, but it is expensive. Furthermore, long-term usage of anticoccidial medications resulted in drug resistance (El Banna et al, 2016). There are also concerns regarding food safety and public health as a result of medicine residues in animal products, which motivates researchers to seek safer alternatives (Wunderlich et al, 2014).…”
Section: Introductionmentioning
confidence: 99%